Outcomes Following Orbital Floor Fractures in the Elderly. Issue 5 (July 2020) - Patel, Alap U.; Haas, Jacqueline A.; Skibba, Kathryn E.; Morrison, Clinton S.
Abstract : Background: Orbital floor fractures in the elderly are controversial, with varying guidelines on indications for operative and nonoperative management. Morbidity includes changes to ocular position, inferior rectus muscle injury, and damage to the neurovascular bundle as it traverses the orbital floor. Across all facial fractures, the elderly are less frequently operated on, albeit longer hospital stays and more probably ICU admission. This study's purpose is to describe our experience with orbital floor fractures and the role of operative versus nonoperative management in the context of patient age. Methods: Retrospective review of orbital floor fracture coronal and sagittal CT images between 2015 and 2018 in those aged 20 to 40 (controls) or over 65 (cases). Patients were excluded if imaging revealed additional complex fractures of the upper third of the face or the midface. Results: Twenty-five subjects met inclusion criteria for the elderly cohort (mean age of 79.4 years) compared to 48 subjects included in the control cohort (mean age 29.9). In the elderly population the most common mechanisms of injury were mechanical fall (72%) and syncope (8%), compared to assault (69%) and MVC (13%) in the controls. Two elderly patients (8%) required operative repair of their injury, whereas fourteen had surgery (29%) in the control cohort. Overall, the mean elderly fracture size was 3.19 cm 2 (SD 1.18) and the mean control fracture size was 2.83 cm 2 (SD 1.67) ( P   =  0.37 ) . Within the elderly group, the mean fracture size for those who underwent surgery was 3.5 cm 2 compared to 3.2 cm 2 in those treated non-operatively ( P   =  0.27). Within the control group, the mean fracture size for those who underwent surgery was 2.9 cm 2 compared to 2.8 cm 2 in those treated non-operatively ( P   =  0.25). Conclusions: Orbital floor fractures in the elderly do not require operative intervention in most instances for management. Abstract : Supplemental Digital Content is available in the text